Respuesta :
。☆✼★ ━━━━━━━━━━━━━━ ☾
8x^2 + 5x - 4 = 2x^2 - 8x + 1
Move everything on the right side to the left by using inverse ops
6x^2 + 13x - 5 = 0
Use the quadratic answer to get your answers of:
x = [tex]\frac{-6+\sqrt{66} }{6}[/tex] , x = [tex]\frac{-6-\sqrt{66} }{6}[/tex]
Have A Nice Day ❤
Stay Brainly! ヅ
- Ally ✧
。☆✼★ ━━━━━━━━━━━━━━ ☾
Answer:
[tex]x = - \frac{5}{3} \: \: \: \: \: \: \: x = - \frac{1}{2} \\ [/tex]
Step-by-step explanation:
[tex]8x {}^{2} + 5x - 4 = 2x {}^{2} - 8x + 1 \\ 8x {}^{2} - 2x {}^{2} + 5x + 8x = 4 + 1 \\ 6x {}^{2} + 13x = 5 \\ [/tex]
now splitting
[tex]6x {}^{2} + 13x - 5 = 0 \\ 6x {}^{2} + 3x + 10x - 5 = 0 \\ 3x(2x + 1) + 5(2x + 1) = 0 \\ (3x + 5)(2x + 1) \\ x = - \frac{5}{3} \: \: \: \: \: \: \: x = - \frac{1}{2} [/tex]